Kajian Dan Evaluasi Terhadap Perilaku Transgender Dari Perspektif Etika Kristen - Yosia Belo (JURNAL LUXNOS, 2021)
Abstract: This research is about the study and evaluation of transgender behavior from the perspective of Christian ethics. The interest in researching this topic arose from the proliferation of broadcasts by transgender groups on social media such as Facebook and YouTube. Where the broadcast received a good response from the public, as if the community justified their every behavior. That is why through this research, transgender behavior will be studied and evaluated in order to contribute ideas to Christians. In this study it was concluded that transgender behavior is behavior that is against the principles and teachings of the Bible, behavior that arises from the consequences of sin, and behavior that must be prohibited, but for victims they must be loved so that they become aware and repent and return to correct, normal sexual behavior and glorify Allah. Abstrak: Penelitian ini adalah tentang kajian dan evaluasi terhadap perilaku transgender dari perspektif Etika Kristen. Ketertarikan meneliti topik ini muncul dari maraknya tayangan kelompok transgender pada media sosial seperti facebook dan youtube. Di mana tayangan itu mendapat sambutan yang baik dari masyarakat, seolah-olah masyarakat membenarkan setiap perilaku mereka. Itulah sebabnya melalui penelitian ini akan dikaji dan dievaluasi perilaku transgender guna menjadi sumbangsih ide kepada orang-orang Kristen. Pada penelitian ini disimpulkan bahwa perilaku transgender adalah perilaku yang bertentangan dengan prinsip dan ajaran Alkitab, perilaku yang muncul dari akibat dosa, dan perilaku yang harus dilarang namun bagi para korban harus tetap dikasihi supaya mereka sadar dan bertobat serta kembali kepada perilaku seksual yang benar, normal dan mempermuliakan Allah.